Heart of the Country - Kamerling, Len (Journal of Anthropological Films, 2023)
How can we create a world that will offer our children wisdom, humanity, responsibility and hope? Shinichi Yasutomo, the extraordinary principal of a rural village school in Hokkaido, Japan, passionately believes he knows the way - by giving children a moral compass to guide their lives, by educating their hearts as wells as their minds. Heart of the Country takes time - a full calendar year, to follow the life of this extraordinary man and the families and children he has dedicated himself to. It is also the story of the village of Kanayama, a rural farming community bound together by love for its children and a deep respect for learning. Parents, elders and leaders of this once impoverished town have been tempered by the long journey through the cultural upheaval of postwar Japan. They embrace Principal Yasutomo’s vision of hope for the future, but not without wary glances back to the past. Produced in collaboration with the community of Kanayama, Hokkaido and the Hokkaido University of Education Japan.